Design and in vivo activity of A(3) adenosine receptor agonist prodrugs - Suresh, R. Rama (Purinergic Signal, 2020)
Prodrugs (MRS7422, MRS7476) of highly selective A(3) adenosine receptor (AR) agonists Cl-IB-MECA and MRS5698, respectively, were synthesized by succinylation of the 2′ and 3′ hydroxyl groups, and the parent, active drug was shown to be readily liberated upon incubation with liver esterases. The prodrug MRS7476 had greatly increased aqueous solubility compared with parent MRS5698 and was fully efficacious and with a longer duration than MRS7422 in reversing mouse neuropathic pain (chronic constriction injury model, 3 μmol/kg, p.o.), a known A(3)AR effect. MRS7476 (5 mg/kg, p.o., twice daily) was found to protect against non-alcoholic steatohepatitis (NASH) in the STAM mouse model, indicated by the NAFLD activity score. Hepatocyte ballooning, IL-10 production, and liver histology were significantly normalized in the MRS7476-treated mice, but not liver fibrosis (no change in ACTA2 levels) or inflammation. Hepatic expression of ADORA3 in human NAFLD patients was 1.9-fold lower compared to normal controls. Adora3 expression determined by qPCR in primary mouse liver was associated with the stellate cells, and its mouse full body A(3)AR knockout worsened liver markers of inflammation and steatosis. Thus, we have introduced a reversible prodrug strategy that enables water solubility and in vivo activity of masked A(3)AR agonists in models of two disease conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11302-020-09715-0) contains supplementary material, which is available to authorized users.